European Actorness in a Shifting Geopolitical Order European Strategic Autonomy Through Differentiated Integration - Rieker, Pernille (The European Union in International Affairs, 2024)
This is an open access book. With the unprovoked Russian invasion of Ukraine, European security has been put on high alert. The implications of the Russian military invasion are many and difficult to grasp in full. However, the need for greater European strategic autonomy appears increasingly evident. The book argues that strategic autonomy may be reached-also in the short run-if differentiated integration is seen as an asset rather than a challenge. While the EU (together with NATO) remains the core in such a system, there is a multitude sub-regional integration processes that need to be taken into account to get the full idea of how European strategic autonomy can be achieved.